Topics in current aerosol research - Hidy, G. M.; Brock, J. R. (International reviews in aerosol physics and chemistry, 1971)
Topics in Current Aerosol Research deals with the fundamental aspects of aerosol science, with emphasis on experiment and theory describing highly dispersed aerosols (HDAs) as well as the dynamics of charged suspensions. Topics covered range from the basic properties of HDAs to their formation and methods of generation; sources of electric charges; interactions between fluid and aerosol particles; and one-dimensional motion of charged cloud of particles. This volume is comprised of 13 chapters and begins with an introduction to the basic properties of HDAs, followed by a discussion on the form.